Short Note: Earthquake families in the seismicity of Popocatépetl volcano - Z. Jiménez; A. Zamora-Camacho; J. M. Espíndola (Geofísica Internacional, 2005)
Analysis of the seismicity of Popocatepétl volcano (Central Mexico) over the period September 1 to December 31, 1995, shows the existence of three earthquake families, with correlation coefficients better than 0.5 in all components of three stations. For two families the events have similar magnitudes and occur over a relatively long period of time. This suggests that they are of the asperity type. They occur up to a depth of 4 km below sea level underneath the volcano, and may be generated by the passage of magma through the upper volcanic conduits.